Pengaruh Kompetensi dan Mindset Terhadap Kesiapan Mahasiswa Memasuki Dunia Kerja Di Era 4.0 - Milania Ramadhani; Pardiman Pardiman; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine and analyze the simultaneous influence of mindset and competence variables on job readiness, to analyze the influence of mindset on job readiness, and to determine and analyze the effect of competence on job readiness. This type of research uses quantitative research. The population in this study were management students of class 2018 using probability sampling technique with the results of calculations using the formula, the number of samples used was 85 respondents. Data collection techniques using a questionnaire. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, t-test, F-test and the Coefficient of Determination which is processed using the SPSS software program. Keywords: Competence, Mindset And Work Readiness